"But there is always hope in the human heart": Italian Jews' Search for the Deported in the Immediate Aftermath of the Holocaust. (17th November 2020) - Koch, Anna
Abstract: This investigation examines the early efforts of Italian survivors, beginning with the June 1944 liberation of Rome, to discover the fate of loved ones. Survivors of the camps shared their experiences with those who had evaded capture and deportation (through hiding, passing, or other means). Highlighting the crucial role returnees played in transmitting information about the camps reveals how these two groups created support networks. As hope that relatives would return dwindled by the late 1940s, this frantic search evolved into an effort to commemorate the victims. Though relatives struggled to mourn without a body to bury or grave to visit, networks of shared suffering and early attempts to commemorate the deceased helped survivors process their loss.